Pengaruh Konfigurasi Spasial dan Tata Letak Bangunan terhadap Perilaku Eco-Campus Mahasiswa Universitas Negeri Gorontalo - Irwan Wunarlan (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the influence of spatial configuration and building layout on the behavior of student eco-campus at Gorontalo State University. The study used a quantitative approach with a correlational method to identify the relationship between the variables studied. The research population consisted of 22,252 active students of Gorontalo State University, with a sample of 280 respondents determined using the Slovin formula. Data was collected through a Likert scale-based questionnaire and analyzed using multiple linear regression techniques with the help of SPSS software. The results of the analysis showed that spatial configuration had a positive and significant influence on the behavior of the student eco-campus with a significance value of 0.000 and a regression coefficient of 0.412. Similarly, the layout of the building was proven to have a positive and significant influence with a significance value of 0.000 and a regression coefficient of 0.487. Simultaneously, the two independent variables showed a significant influence on eco-campus behavior, which was shown by the calculated F-value of 141.558 with a significance level of 0.000. These findings indicate that the quality of campus spatial arrangement, ease of access, the existence of green open spaces, circulation systems, and the availability of integrated environmental facilities play a role in encouraging the formation of environmentally friendly behavior of students. Therefore, the development of campus design that is oriented to sustainability principles can be one of the important strategies in strengthening the implementation of eco-campuses in the university environment.